Five-Factor Model Personality Traits and Inflammatory Markers: New data and a meta-analysis - Luchetti, Martina (Psychoneuroendocrinology, 2014)
The purpose of this research is to examine the association between five major dimensions of personality and systemic inflammation through (a) new data on C-reactive protein (CRP) from three large national samples of adults that together cover most of the adult lifespan and (b) a meta-analysis of published studies on CRP and interleukin-6 (IL-6). New data (total N=26,305) were drawn from the National Longitudinal Study of Adolescent Health, the Midlife in the United States study, and the Health and Retirement Study. PRISMA guidelines were used for the meta-analysis to combine results of up to seven studies on CRP (N=34,067) and six on IL-6 (N=7,538). Across the three new samples, higher Conscientiousness was associated with lower CRP. The Conscientiousness-CRP relation was virtually identical controlling for smoking; controlling for body mass index attenuated this association but did not eliminate it. Compared to participants in the highest quartile of Conscientiousness, participants in the lowest quartile had an up to 50% increased risk of CRP levels that exceeded the clinical threshold (≥3mg/l). The meta-analysis supported the association between Conscientiousness and both CRP and IL-6 and also suggested a negative association between Openness and CRP; no associations were found for Neuroticism, Extraversion and Agreeableness. The present work indicates a modest, but consistent, association between Conscientiousness and a more favorable inflammatory profile, which may contribute to the role of Conscientiousness in better health across the lifespan.